Isolation and Identification of Endophytic Fungi from leaves and petioles of Salam Plants (Syzygium polyanthum Wight) to Look for Antibiotic-Producing Fungi - Yudiarti, Turrini; Tri Agus Sartono; Endang Widiastuti; Hanny Indrat Wahyuni; Sugiharto; Ika Agusetyaningsih (Al-Hayat: Journal of Biology and Applied Biology, 2025)
Synthetic antibiotics have been used to stimulate livestock growth. Because of the negative impact of using these material, it is necessary to find its substitute. One of the producer of natural antibiotics is microorganisms such as fungus. Endophytic fungi are one kinds of fungi that live in plant tissues and able to form colonies without endangering the host and can produce secondary metabolites such as antibiotic. This study is preliminary research that the ending of the purpuse is to find the endophytic fungi which producing antibiotic. This first aims of the study is to psolation and identification of the endophytic fungi found on leaves and petioles of Salam (Syzygium polyanthum Wight). The materials used are leaves and petioles of Salam which are obtained from traditional markets. The method was the isolation by direct planting used spread methods, then continue to identification. The results was the isolation of endophytic fungi from the Salam plant parts obtained as follows from leaves got five isolates and from petiole are seven isolates. Identification of all isolates found as follows from leaves are Mycelia sterilia, Acremonium sp and Fusarium sp and from petioles were Mycelia sterilia , Fusarium sp, Aspergillus sp and unidentified fungi. Keywords: endophytic fungi, antibiotics, petiols, leaves, Syzygium polyanthum